2008
DOI: 10.1002/fld.1737
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a parallel multigrid solver for the simulation of spreading droplets

Abstract: SUMMARYWe consider the parallel application of an efficient solver developed for the accurate solution of a range of droplet spreading flows modelled as a coupled set of nonlinear lubrication equations. The underlying numerical scheme is based upon a second-order finite difference discretization in space and a secondorder, fully implicit, adaptive scheme in time. At each time step, this leads to the need to solve a large system of nonlinear algebraic equations, for which the full approximation storage multigri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…As described in the introduction, this is an extremely important class of numerical algorithm which, due to its computational efficiency, is becoming more and more widely used in practical engineering software. Illustrative work includes [9,[11][12][13]16,19,20,28], but there are many more examples that could be cited. The original multigrid approach, e.g.…”
Section: Related Workmentioning
confidence: 98%
See 2 more Smart Citations
“…As described in the introduction, this is an extremely important class of numerical algorithm which, due to its computational efficiency, is becoming more and more widely used in practical engineering software. Illustrative work includes [9,[11][12][13]16,19,20,28], but there are many more examples that could be cited. The original multigrid approach, e.g.…”
Section: Related Workmentioning
confidence: 98%
“…In particular we consider heterogeneous and multicore processor architectures, combined with different communication architectures, such as Myrinet and Fast Ethernet switching. Furthermore, unlike our previously published work [23][24][25]27], we demonstrate the effectiveness of our approach on practical engineering software [12,13], in addition to codes that are based upon slightly less complex mathematical models [11].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Examples include flow over homogeneous substrates with, Schwartz et al (2001), and without, Glass et al (2010), evaporation, with surfactants, Schwartz et al (2004) and for a non-Newtonian power-law liquid, Ahmed et al (2013), over heterogeneous substrates with variable wettability, Schwartz & Eley (1998) and containing in addition micro-scale topographical features, Gaskell et al (2004). A key challenge is achieving mesh independent solutions, Koh et al (2009), and spreading rates quantitatively comparable with those observed experimentally, Gaskell et al (2008).…”
Section: Introductionmentioning
confidence: 97%
“…Important examples are encountered in the deposition of coatings and inks, in enhanced oil recovery, the direct patterning of functional layers during microchip production and the cooling of electronic components, see for example Bear (1988); Gaskell et al (2008); Anandan & Ramalingam (2008).…”
Section: Introductionmentioning
confidence: 99%